Economic Impact Analysis of Relocation Five Feet Vendors in Purwokerto - Purnomo, Rochmat Aldy (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This study aimed to analyze income, expenses, and social environment of street vendors between before and after the relocation to Pratistha Harsha. Collecting data is using interview, observation and literature study techniques. The respondents were selected namely Pratistha Harsha Chief Manager, Chairman of The Pratistha Harsha Society, Pratistha Harsha vendors culinary. Population of street vendors who relocated to Pratistha Harsha are 65 peoples and sample are 40 seller respondents. Selection of the sample is using simple random sampling. The study was conducted in September 2015 and using a paired t test analysis. The results show that the amount of production is lower after the relocation, and sales turnover and net income are not different between before and after the relocation to Pratistha Harsha. In the aspect of cost, there are improvement after relocating to Pratistha Harsha.